Conservantes artificiales en alimentos procesados y su incidencia en la salud de las personas - Ayala Lara, Nayeli Lisseth (2024)
Artificial preservatives are mostly considered safe, but several have negative, carcinogenic and toxic side effects. Preservation methods are the best way to maintain the quality of food and prevent its deterioration. Nowadays, various types of preservation methods are available that can be used to maintain the quality of food products for a long period of time, whether using conventional or modern preservation technology methods, some of these preservation methods use additional food preservatives that can be classified into the category of artificial and natural preservatives. For this case study, three specific artificial preservatives are investigated, in this case it is about Nitrites and nitrates, Sodium benzoate and Potassium sorbate. On the other hand, the negative effects of three types of artificial preservatives on health are analyzed. It also points out the gaps in information and areas of research that are required to evaluate the benefits and risks of these preservatives. In addition, it presents aspects related to the long-term consequences of its consumption for human health.